Evaluation of the Implementation of the Inclusive Education Program at Sint Yoseph Elementary School, Central Jakarta, DKI Jakarta Province - daru, maria (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The purpose of this study was to evaluate and find the inequality in the implementation of the inclusive education program at SD Sint Yoseph. Despite having a strong commitment, SD Sint Yoseph has experienced a decrease in the number of students with special needs in the last three years. In 2022, there were 6 students with special needs, in 2023 there were 4 students with special needs, and in 2024 there were 3 students with special needs. This decline is a concern for schools to evaluate the effectiveness of the implementation of the inclusive education program that has been implemented. The research design model used is the Discrepancy Evaluation Model (DEM) model. This study uses an evaluative research design with a quantitative-descriptive approach. This research design was chosen with the consideration of evaluating the implementation of the Inclusive Education program in Elementary Schools. The evaluation subjects used as providers of information or clarity of research data are people who are directly involved in the implementation of the inclusive education program, namely: principals, teachers, parents of students and students. Evaluation of the implementation of the Inclusive Education program at Sint Yoseph Elementary School as follows; Schools have difficulty in recruiting human resources who have special education qualifications or extraordinary education, the implementation of the school's inclusive education program does not yet have partnerships with other parties, the addition of a team of experts and the implementation of training/coaching can accommodate sharing of educators.